FAKTOR-FAKTOR YANG MEMENGARUHI KEIKUTSERTAAN IMUNISASI DPT HB HiB 4 BAYI DI BAWAH DUA TAHUN (BADUTA) DI KABUPATEN GAYO LUES PROVINSI ACEH - Kasmaniar .; Erika Revida; Putri Ayu Yessy Ariesca; Nurcahaya Nainggolan; Uswatun Hasanah (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
Immunization is an effort to actively create/increase a person's immunity against a disease so that if one day they are exposed to that disease they will not get sick or only experience mild illness. The aims of the research to analyze the factors that influenced participation in DPT HB HiB immunization for 4 babies under two years (baduta) in Gayo Lues district, Aceh Province last year. The type of the research used a correlative descriptive research design with a cross-sectional approach, the population is 40 respondents in the Gayo Lues district area, using a total sampling technique the data was obtained from the results of interviews by distributing questionnaires that had been prepared by the researcher. The Data of analysis was carried out univariately and bivariately with an independent t-test and with an alpha (a) value of 0.05. The results of the research showed that there was no influence of family support on DPT HB Hib 4 immunization for babies under two years old (BADUTA) in Gayo Lues district, Aceh province last year. The influence of community empowerment on DPT HB Hib 4 immunization for babies under two years (BADUTA) in Gayo Lues district, Aceh province last year. Then. There was an influence on the role of recording and reporting on DPT HB Hib 4 immunization for babies under two years old (BADUTA) in Gayo Lues district, Aceh province last year.